Investigation of Microbial Contamination of Primary Schools in Baghdad City - Oleiwi , Sanaa Rahman (Iraqi Journal of Science, 2022)
A microbial contamination of several primary schools (official and private) inBaghdad city was conducted. Sampling was performed in each school from desk,door handle, and hand of students.Out of 113swabs (classes desk, door holder, and students hands ) obtained fromten primary schools, growth wasobserved in 91 samples (80.5%) (for officialschool 84.6% and 71.4 for private school.The results of recent study revealed that the official schools showed highercontamination levels(130 CFU ) than private ones (90 CFU).Resultes revealed that a total of 12 morphologically different bacterial specieswere isolated from 62 bacterial isolates,among which gram negative bacteria 40isolates(64.5%) were higher than gram-positive bacteria 22 isolates( 35.4%).According to the microscopic examination , biochemical tests and API system ,the results was showed that staphylococcus epidermidis was the most frequentlyisolated bacterial species with recovery rate 10 (16 .1%). followed bystaphylococcus aureus 8 ( 12.9 %) Escherichia spp7 (11.2%) Escherichia coli7(11.2%), Enterobacter sakazaki 5(8%), Enterobacter cloacae 5 (8%), Bacillus spp5(8%), Pseudomonas aeruginosa 4(6.45%), Klebsiella spp 4(6.45%), Klebsiellapneumoniae 3(4.8%), Streptocoocus spp 3(4.8%), Proteus mirabilis 1(1.6%).